The Impact of Crossbreeding in The Artificial Insemination Program on Reproductive Performance of Beef Cattle - Kusuma Diwyanto; I Inounu (Indonesian Center for Animal Research and Development, 2009)
Artificial Insemination (AI) in beef cattle in Indonesia is widely practised. Nowadays, the goal of AI program is not clear; whether to produce: composite breed; terminal cross or as a commercial animal. In fact, farmer assisted by inseminator do the grading up toward Simmental or Limousine. In this paper, crossbreeding impact on reproductive performance of beef cattle in Indonesia is discussed. Farmers prefer the crossbred cattle resulted from AI because its male offspring has higher price than that of local breed. However, 50% of the offspring are female and are used as replacement stock. This AI practice resulted bigger cattle that need more feed. In the scarce feed condition, this bigger cattle become skinny and in bad shape. This leads to bad reproductive performance such as high ‘service per conception’ (S/C), 'long calving interval' and 'low calf crop'. Moreover, it produces less milk and results in high mortality rate of the offspring. In good management condition, crossbred cattle shows good performance, but often ‘day open’ is longer, since weaning time is postponed. That is why long calving interval still exists eventhough the S/C is low. Local cattle are very adaptive, resistant to tropical diseases and have high reproductive rate, high quality of leather and good quality of carcass. In scarce feed condition, local cattle are skinny but still can show estrous and get pregnant. In bad condition, they produce very small offsprings that die because of lack of milk from the cow. The availability of feed supply both in quantity and quality is the key factor in AI practices to maintain good body condition of crossbred and to produce good quality of offspring. Key words: Artificial insemination, crossbreeding, reproduction, beef cattle